PENGEMBANGAN MEDIA PUZZLE PANCASILA DI KELAS I SDN PANGGUNG LOR BERDASARKAN GAYA BELAJAR KINESTETIK - Rahmawati, Indriani Nur; Kartinah, Kartinah; Prayitno, Muhammad; Susilowati, Deny (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
The purpose of this research is to find out feasible of the puzzle Pancasila media in class I at SDN Panggung Lor based on kinesthetic learning styles. The development of the puzzle Pancasila media uses R&D methods. The development stages adapted the 4D model from Thiagarajan, that is Define, Design, Develop, and Disseminate. Methods of data collection in this reseach using observation, interviews, and questionnaires. The overall results of the feasibility test of this development research produced the puzzle Pancasila media product with the details of (1) media expert test obtained very feasible criteria with a result of 93.88%, (2) the material expert test obtained very feasible criteria with a result of 93.13%, (3) student responses obtained very feasible criteria with a result of 95%. Based on these results, the Puzzle Pancasila media is very feasible for use in SDN Panggung Lor.